Performance assessment and the factors inhibiting the performance of Buddhist education teachers in the teaching duties - Hesti Sadtyadi (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2018)
This research aims to examine the components and inhibiting factors of the teacher’s work performance in the teaching assignments of Buddhist education teachers. The authors believe that the theoretical as well as the practical problems of Buddhist education teachers can be solved by examining its components and the inhibiting factors. This research was developmental research that begins by compiling the component of performance instrument and the inhibiting factors instrument through Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). The data were then analyzed through regression analysis. The subjects of research were Buddhist education teachers in Central Java, Indonesia. The results of the research show the values of Anti-image 0.5 for 7 indicators. Meanwhile, the loading factor was bigger than 0.5 for each component. The model had RMSEA ≤ 0.05, Chi-Square (X²) 0.05, P = 0.55, the GFI was 0.97, which means the model was fit. The teaching performance components of Buddhist education teacher include planning the learning program, implementing the learning program, and evaluating the learning program. The inhibiting factors of the teacher’s performance are the additional tasks, the classroom atmosphere, conflict, and work pressure. This research has proved that the inhibiting factors have a negative impact on the teaching performance of Buddhist education teachers.